QUALITY OF LIFE AND PHYSICAL ACTIVITY LEVEL OF AMPUTEES (Fiep Bulletin - online, 2014)
This research had as an objective characterize and analyze the quality of life and the level of Physical Activity of amputees. The study was classified as a descriptive and diagnostic field research, being developed through quantitative procedures of collection and analysis of the data. The participants were selected according to criteria of the participants own intention, being them amputated of superior and/or lower limb, having the intention of participating on the study and agreeing on publishing the data for scientific purposes, totalizing 10 individuals. The procedures were submitted and approved by the Ethics Committee of Research in Human Beings CEPSH / UDESC, and by the institution involved. The collection of the data was accomplished through the WHOQOL and the IPAQ instruments, between September and October of 2006 and the data were analyzed through the descriptive statistics. The results indicate, in a specific matter, that the amputees are characterized as being "very active" as they present equal or superior physical activity levels of what is suggested by the World's Health Organization especially on the moderate physical activity and on the house duties. Still related to the specific matter, the participants' quality of life is considered as "very good", as it presents positive aspects on the social relationship domain, and positive and negative aspects on the psychological domain, physical domain and environmental domain. The results indicate in a general matter that the amputees are satisfied with their quality of life and that they can be considered as very active as most of the domains that compose the quality of life present positive scores, as well as the fact that they present physical activity levels above the recommended criteria, diverging from the specialized literature that indicates physical activity levels bellow the recommendation for the general population.
Keywords: Amputations; Quality; of Life; Physical Activity Level